New species of Neotanais Beddard, 1886 (Crustacea, Tanaidacea) from the deep sea of the tropical and southern East Atlantic Ocean - Weigmann, Simon; Guerrero-Kommritz, Jürgen (Zootaxa, 2009)
As part of the sampling efforts during the DIVA-II expedition several Tanaidacea of the genus Neotanais were captured in the Guinea and the Cape Basin in the tropical and southern East Atlantic Ocean. Two different species were sampled, Neotanais rotermundiae sp. n. from the Guinea and Neotanais guskei sp. n. from the Cape Basin. The distribution of both species is limited to these basins. A full description for both species is presented. Neotanais guskei sp. n. is the largest Neotanais reported for the South Atlantic Ocean.